Epidemiology of gastric cancer and perspectives for prevention - MUÑOZ NUBIA; FRANCESCHI SILVIA (Instituto Nacional de Salud Pública, 1997)
The most recent estimates of the world-wide incidence of cancer indicate that gastric cancer was in 1990 the second most frequent cancer in the world (after lung cancer), with about 900 000 new cases diagnosed every year. Steady declines in the rates have been observed everywhere in the last few decades, but the absolute number of new cases per year is increasing mainly because of ageing of the population. The exact causes of the decline of gastric cancer are not well understood, but must include improvements in diet, food storage (e.g., refrigeration) and, possibly, the decline of Helicobacter pylori infection. Dietary modifications and, possibly, vitamin supplements remain one of the most important tool for the prevention of gastric cancer. Control of H. pylori infection, by means of eradication or immunization, is also likely to offer great potential for the prevention of this important malignancy.